Społeczna odpowiedzialność jako metoda doskonalenia działalności małych i średnich przedsiębiorstw - Rogala, Piotr (Annales. Etyka w Życiu Gospodarczym, 2009)
The rule of Continuous Improvement is one of the pillars of the concept of Total Quality Management. It states that one should continuously seek the sources of arising problems and eliminate or minimize them. The article presents a method of implementing the concept of Corporate Social Responsibility based on the above rule and afterwards it identifies the most important advantages of using the rule. The article also stresses its usefulness in the area of Small and Medium-sized Companies.